Analysis of Misconceptions in View of Gender Differences in Chemistry Learning - Kristyasari, Marantika Lia; Kusumaningrum, Idha Ayu (Universitas Sebelas Maret, 2023)
Misconceptions refer to students' incorrect understanding of a concept, which can lead to difficulties in problem-solving activities. This study aimed to examine the misconceptions of high school students regarding gender differences. The research was conducted in a selected high school, using a purposive sampling technique to select a class with above-average academic achievement. The research used a quantitative descriptive method and analyzed the data using GRM scoring. The findings showed that the average percentage of misconceptions held by students in all competency indicators was 28% for females and 22% for males. Misconceptions were found in all four competency indicators for buffer solution materials, including explaining the meaning of components, the working principle of buffer solutions, the role of buffer solutions in everyday life, and calculating the pH of buffer solutions. The highest percentage of misconceptions for both females and males was found in the first competency indicator, with 47% and 56%, respectively.